VD_FINDINFO Jug / 2014 / 96 vom 16. April 2014 - VD Tribunal cantonal (2014)
DIVORCE, PARTAGESENS GÉNÉRAL, PRESTATION DE LIBRE PASSAGE, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 122 al. 1 CC, 22 al. 1 LFLP, 7 OLP, 8a al. 1 OLP, 12 OPP2, 111 al. 1 LPA-VD